The impact of blockchain on the aviation industry - Pinto Lopes, Daniel (2021)
Pinto Lopes, D., Rita, P., & Treiblmaier, H. (2021). The impact of blockchain on the aviation industry: Findings from a qualitative study. Research in Transportation Business and Management, 41(December), 1-12. [100669]. https://doi.org/10.1016/j.rtbm.2021.100669